EVALUASI PROGRAM UJIAN AKHIR MADRASAH BERSTANDAR NASIONAL BERBASIS KOMPUTER (UAMBN-BK) PADA MADRASAH ALIYAH MAKRIFATUL ILMI BENGKULU SELATAN - Anwar fathoni (Manajer Pendididikan, 2020)
The theoretical research objectives are used to obtain overall data from a) Evaluation of planning for implementation; b) evaluation of implementation; and c) evaluation of exams at Madrasah Aliyah Makrifatul Ilmi. This research method is a program evaluation evaluation test, while data collection techniques are carried out by interview, observation and documentation. The research subjects were the school principal, deputy head of the curriculum, school operators and technicians. The results of the evaluation study of the implementation of the exam are: At the planning stage of the exam in schools include facilities and infrastructure, the determination of officers and technicians, preparation of Standard Operating Procedures; at the stage of the implementation of examinations in schools that must be done three times starting from try out, rehearsal and conducting the exam, at the stage of evaluating the results of the exam is the responsibility of the central level committee and distributed to each school through the application of printed test results.Keywords : The planning, Implementation, Assessment, Evaluation, Exam Abstract: Tujuan penelitian secara teoritis digunakan untuk memperoleh data keseluruhan dari a) Evaluasi perencanaan untuk implementasi; b) evaluasi implementasi; dan c) evaluasi ujian Madrasah Aliyah Makrifatul Ilmi. Metode penelitian ini adalah tes evaluasi evaluasi program, sedangkan teknik pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala kurikulum, operator sekolah dan teknisi. Hasil studi evaluasi pelaksanaan ujian adalah: Pada tahap perencanaan ujian di sekolah meliputi sarana dan prasarana, penentuan petugas dan teknisi, persiapan Prosedur Operasional Standar; pada tahap pelaksanaan ujian di sekolah yang harus dilakukan tiga kali mulai dari try out, gladi bersih dan ujian utama, pada tahap mengevaluasi hasil ujian adalah tanggung jawab komite tingkat pusat dan dibagikan ke masing-masing sekolah melalui penerapan hasil tes yang dicetak. Kata Kunci : Perencanaan, Implementasi, Penilaian, Evaluasi, Ujian